As per the given question,
focal length of the lenses are "(f_1)=8.5cm"
"f_2=5.5cm"
Distance between the lenses are "(d)=36cm"
Hence focal length of the lens will be "\\frac{1}{f}=\\frac{1}{f_1}+\\frac{1}{f_2}-\\frac{36}{f_1f_2}"
Now, substituting the values,
"\\frac{1}{f}=\\frac{1}{8.5}+\\frac{1}{5.5}" "-\\frac{36}{8.5\\times 5.5}"
"\\Rightarrow \\frac{1}{f}=\\frac{56}{187}-\\frac{144}{187}"
"\\Rightarrow \\frac{1}{f}= \\frac{-88}{187}cm"
"\\Rightarrow f= \\frac{-187}{88}cm"
Comments
Leave a comment